Knowledge and attitudes towards cervical cancer and screening among migrant women: a qualitative study in Portugal - Inês Fronteira; Patrícia Marques; Sónia Dias; Ana Gama; Joana Silva (BMJ Open)
Objective To explore the perceptions of migrant women, healthcare professionals and community workers regarding migrant women’s knowledge and attitudes about cervical cancer (CC) and screening and how these influence cervical cancer screening (CCS) uptake.Design Qualitative study with seven focus groups, using a semistructured guide.Setting Five focus groups were conducted online and two in community associations in Lisbon, Portugal.Participants This study included 23 migrant women, 12 healthcare professionals and 10 community workers.Results A lack of knowledge and negative attitudes towards screening among migrants were discussed as important factors leading to a lower CCS uptake. For participants, many migrant women are unaware of the disease and CCS. Feelings of uneasiness related to screening and reservation from their husbands towards consultations underlie negative attitudes towards CCS. Disparities among migrant women regarding uptake of CCS rooted on sociocultural factors were highlighted, with women from African origin and older tending to engage less. Healthcare professionals were identified as the preferred source of information; nevertheless, difficulties in delivering information on sensitive topics were reported by professionals. Additionally, participants agreed that peers and social networks may play a role in promoting screening among communities.Conclusions Healthcare professionals and community actors are paramount to promote CCS among migrant women, especially through culturally adapted awareness interventions and health-promoting activities engaging local communities and social networks of women. Training on cross-cultural communication skills of healthcare professionals may contribute to improving migrant women’s knowledge and uptake of CCS.